From fitness trackers to medical devices: wearable technologies - Zhi Zhou (Big Data and Computing Visions)
Wearable technology, wearables, fashion technology, smart wear, skin electronics, or fashion electronics are smart electronic devices. Wearable technology has various applications that grow as the field expands. It appears prominently in consumer electronics with the popularization of the smartwatch and activity tracker. A popular activity tracker called the fit bit is widely used in the fitness industry to track calories and health-related goals. A popular smartwatch in the market is the Apple Watch. Apart from commercial uses, wearable technology is incorporated into navigation systems, advanced textiles, and healthcare. As wearable technology is being proposed for critical applications, it must be vetted for its reliability and security properties. Applications based on Wireless Sensor Networks (WSN) for Internet of Things (IoTs) scenarios are rising. The multiple possibilities they offer have spread towards previously hard-to-imagine fields, like e-health or human physiological monitoring. An application has been developed for its usage in scenarios where data collection is applied to smart spaces, aiming at its usage in firefighting and sports. This application has been tested in a gymnasium with real, non-simulated nodes and devices. A graphic user interface has been implemented to suggest a series of exercises to improve a sportsman/woman s condition, depending on the context and their profile. This system can be adapted to a wide variety of e-health applications with minimum changes, and the user will interact using different devices, like smartphones, smartwatches, and/or tablets.